2013
DOI: 10.1093/annonc/mdt141
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pathologic complete response on disease-free survival in patients with esophagogastric adenocarcinoma receiving preoperative docetaxel-based chemotherapy

Abstract: A pCR following preoperative docetaxel/platin/fluoropyrimidine indicates favorable outcome in patients with gastric or EGJ adenocarcinoma. Tumor location in the EGJ is associated with a higher pCR rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
55
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 21 publications
12
55
1
Order By: Relevance
“…In our study, there are 31 patients with ypT0 stage and the 5.9% pCR rate was comparable to the data from previous studies (3-15%) [14][15][16][17][18][19][20]. We found that the DFS and OS of pCR patients were similar to the ypStage I patients.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, there are 31 patients with ypT0 stage and the 5.9% pCR rate was comparable to the data from previous studies (3-15%) [14][15][16][17][18][19][20]. We found that the DFS and OS of pCR patients were similar to the ypStage I patients.…”
Section: Discussionsupporting
confidence: 89%
“…Our data as well as data from three other groups are in strong contrast to the data of Messager et al [24] who could not demonstrate an effectiveness of preoperative chemotherapy in patients with signet ring cell histology [11,15,10,24]. However, two other groups (Fields et al [15] and Ott et al [11]) also included patients treated with radiochemotherapy, and Lorenzen et al [20] showed a decreased percentage of pCR on diffuse-type cancer in comparison to the intestinal type [11,15,20]. Schmidt et al [7] also show a correlation between the Lauren type and histopathological remission grade.…”
Section: Discussioncontrasting
confidence: 91%
“…These results indicate that the hypothesis raised in the cooperative analysis of the AIO [20] of an improved pCR rate and prognosis under preoperative integration of taxanes in comparison to ECF can only be answered in a randomized trial, which is currently conducted by the AIO (Clinical-Trial.gov No. NCT01216644).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A multidisciplinary tumor board, including upper GI surgeons, gastroenterologists, oncologists, and specialized radiologists, determined the therapeutic approach. In patients with adenocarcinoma and suspected lymph node involvement or tumor stage >T3, a perioperative chemotherapy with regimens including 5-FU, epirubicin, and cisplatin or 5-FU and oxaliplatin [8, 9] or docetaxel, cisplatin, and capecitabine [10, 11] was administered. Patients suffering from esophageal squamous cell carcinoma received neoadjuvant systemic therapy with carboplatin and paclitaxel complemented with 41 Gy radiotherapy [12-14].…”
Section: Methodsmentioning
confidence: 99%